Designing fiscal regimes for impact benefit agreements. (August 2021) - Gunton, Cameron; Gunton, Thomas; Batson, Joshua; Markey, Sean; Dale, Daniel
Highlights: We evaluate alternative impact benefit agreement fiscal instruments using a comprehensive set of criteria. No fiscal instrument is ideal in terms of fully meeting all criteria. A multiple account evaluation of revenue and non-revenue provisions of agreements is recommended for assessing trade-offs. The optimal fiscal regime for impact benefit agreements is likely a hybrid design that uses a combination of fiscal instruments.